A new three-level sparse indirect matrix converter - Klumpner, Christian; Lee, Meng Yeong; Wheeler, Patrick (2006)
Matrix converters are forced commutated single stage AC/AC direct frequency changers able to achieve sine wave in and out operation by being able to connect any input phase to any output phase via a 3x3 matrix of bi-directional switches. Indirect two-stage matrix converters provide similar input and output performance with no passive component in the dc-link, some of these topologies requiring less switching devices or achieving multilevel output voltage capability. This paper proposes a new indirect matrix converter topology with a three-level phase to neutral output voltage capability and reduced number of devices. A new Space Vector Modulation scheme with restricted switching states is proposed, being able to provide sine wave input and output, which is validated by simulation results.